Brain-eating Amoebae Infection: Challenges and Opportunities in Chemotherapy - Mungroo, Mohammad R.; Anwar, Ayaz; Khan, Naveed Ahmed; Siddiqui, Ruqaiyyah (Mini Reviews in Medicinal Chemistry, 2019)
Pathogenic free-living amoeba are known to cause a devastating infection of the central nervous system and are often referred to as “brain-eating amoebae”. The mortality rate of more than 90% and free-living nature of these amoebae is a cause for concern. It is distressing that the mortality rate has remained the same over the past few decades, highlighting the lack of interest by the pharmaceutical industry. With the threat of global warming and increased outdoor activities of public, there is a need for renewed interest in identifying potential anti-amoebic compounds for successful prognosis. Here, we discuss the available chemotherapeutic options and opportunities for potential strategies in the treatment and diagnosis of these life-threatening infections.
Keywords: drugs